HISTORICAL ANALYSIS OF URBANITY ON THE WATERFRONT - Karsono, Bambang (Universitas Malikussaleh, 2013)
Since the dawn of the civilization, water plays an important role in human life. Water covers 75% of the earth surface and sustains virtually every life form on it. From the early days of human settlement, the banks of themajor rivers such as the Nile, Tigris, Euphrates, Indus and Hwang Ho became the cradle of civilizations. It is here the culture developed and the pattern and morphology of urban settlement became the source of ourknowledge. This paper attempts to overview the main developmental periods of waterfronts around the world. It discusses on the fundamental periods and events which shaped the city water-borne activities and explained how those events influenced the nature of public space on the waterfronts. The port-city that developed since then will be analyzed corresponding to the historical events that are related to the city development. A few cases studies will be shown in order to present a valuable descriptive situation. Corresponding to the above issues, a continuous process that took place in the development of the waterfront will be discussed extensively.